Envolvimento da neurotransmissão do fator liberador de corticotrofina (CRF) no hipotálamo lateral nas respostas cardiovasculares e comportamentais ao estresse em ratos - Barretto-de-Souza, Lucas (2023)
The lateral hypothalamus (LH) is a hypothalamic area implicated in the integration of physiological and behavioral responses to stress. Indeed, it has been demonstrated the involvement of the LH in cardiovascular responses to stress and in the control of behavioral responses related to anxiety and depression. The corticotropin-releasing factor (CRF) system has been shown to be an important neurochemical mechanism in the central nervous system involved in the etiology of behavioral changes and physiological adjustments induced by exposure to aversive situations. In addition, chronic exposure to aversive situations affects the expression of CRF components in brain regions involved in the control of stress responses. Therefore, the hypothesis of our work was that the CRF neurotransmission present in the LH is involved in the cardiovascular and anxiety-like behavioral changes induced by acute or repeated restraint stress, as well as in the cardiovascular changes induced by chronic variable stress (CVS). Initially, we investigated the effect of bilateral microinjection of the selective CRF1 receptor antagonist CP376395 or the selective CRF2 receptor antagonist antisauvagine-30 (ASV-30) on cardiovascular responses during acute restraint stress. It was identified that microinjection of CP376395 or ASV-30 into the LH decreased the tachycardia response during an acute session of restraint stress, but without altering the pressor responses and tail skin temperature drop. We also compared the effect of LH treatment with CRF1 or CRF2 receptor antagonists on cardiovascular responses during the 1st and 10th session of restraint stress. As observed in the acutely stressed animals, we identified that treatment of the LH with CP376395 or ASV-30 reduced the tachycardia response during the 10th restraint stress session. Furthermore, treatment of the HL with CP376395 increased the tail skin temperature drop response during the 10th restraint session. In addition, we evaluated the involvement of LH CRF1 and CRF2 receptors in the control of anxiety-like behavior induced by an acute or 10 sessions of restraint stress. We identified that treatment of the LH with CP376395 or ASV-30 inhibited the ansiogenic-like effect in the elevated plus maze (EPM) induced by the acute session of restraint stress. We did not identify behavioral changes in the EPM in animals repeatedly subjected to restraint stress, and pharmacological treatments also had no behavioral effect when administered before the 10th restraint session. The evaluation of the influence of the CRF system on the cardiovascular changes induced by CVS indicated that antagonism of either CRF1 or CRF2 receptors in the LH prevented the impairment in baroreflex activity observed in animals subjected to CVS. Finally, the effect of exposure to repeated restraint stress (RRS) or CVS on protein levels of CRF receptors in the LH was assessed. It was observed that RRS had no influence on the levels of both CRF receptors, but CVS caused an increase in CRF2 receptor protein levels, but without altering CRF1 receptor levels. In summary, the data of the present study indicate that CRF neurotransmission in the LH mediates cardiovascular and behavioral responses to acute and chronic stress.